Zum fachphraseologischen Einsatz des Öl-Wortschatzes.: Eine Vorstudie - Russo, Eriberto (Linguistik Online, 2023)
This contribution intends to examine the lexical universe of oil, while paying attention both to production practices (expressions, terms, etc., which are directly related to the production of oil, from the harvest to the packaging phase) and to commercialization practices or expressions etc. used to represent the product from an organoleptic and gustatory point of view. The terminological and phraseological analysis is anticipated by a reflection on the relationship between technical language and phraseology and on the presence of the lexeme Öl in the German language. Excerpts from specialist websites are used to carry out the first terminological and phraseological analysis (concerning the production of oil); the second part of the analysis (product marketing) is carried out by taking the product’s descriptions (different types of oil) of websites into account.